2010
DOI: 10.1371/journal.pgen.1001208
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomere Formation Occurs by the Assembly of Multiple Latent Protein Complexes

Abstract: The stereotyped striation of myofibrils is a conserved feature of muscle organization that is critical to its function. Although most components that constitute the basic myofibrils are well-characterized biochemically and are conserved across the animal kingdom, the mechanisms leading to the precise assembly of sarcomeres, the basic units of myofibrils, are poorly understood. To gain insights into this process, we investigated the functional relationships of sarcomeric protein complexes. Specifically, we syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
97
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(106 citation statements)
references
References 42 publications
9
97
0
Order By: Relevance
“…Knockdown of individual sarcomeric proteins can disrupt sarcomere assembly (Rui et al, 2010). We had previously shown that sarcomeric RNAs were downregulated in hoip 1 embryos at St12-13, and that Mhc protein expression was greatly reduced in St16 hoip 1 embryos (Johnson et al, 2013).…”
Section: Tm2 Regulates Sarcomeric Protein Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Knockdown of individual sarcomeric proteins can disrupt sarcomere assembly (Rui et al, 2010). We had previously shown that sarcomeric RNAs were downregulated in hoip 1 embryos at St12-13, and that Mhc protein expression was greatly reduced in St16 hoip 1 embryos (Johnson et al, 2013).…”
Section: Tm2 Regulates Sarcomeric Protein Expressionmentioning
confidence: 99%
“…First, the myotube must elongate over several cell diameters to identify and contact the appropriate tendon cells (Schnorrer and Dickson, 2004). Second, the myotube must express a wide range of muscle structural proteins and assemble those proteins into contractile sarcomeres (Rui et al, 2010). Although the mechanisms that regulate myotube precursor specification and muscle structural gene transcription have been characterized in detail (Buckingham and Rigby, 2014;Ciglar and Furlong, 2009), the molecules that coordinate myotube elongation are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S3I,J). Sarcomere assembly occurs after myotube elongation and myofiber attachment (Rui et al, 2010) and embryos defective for the first round of myoblast fusion do express MHC (Chen and Olson, 2001). Together, these observations demonstrate that muscle morphogenesis is genetically separable from muscle structural expression and prompted us to define a secondary role for Hoip during myogenesis.…”
Section: Somatic and Cardiac Muscle Maturation Is Hoip Dependentmentioning
confidence: 99%
“…Indeed, the findings from a recent multi-approach study have indicated that the assembly of sarcomeric components into highly ordered structures, including the stereotypic striations, does not occur in a sequential manner, but rather the process is dependent upon the assembly of multiple protein complexes that are preformed (Rui et al, 2010). Knowledge about the mechanisms, which are responsible for maintaining the sarcomeric structures under normal mechanical stress, is however limited.…”
Section: Introductionmentioning
confidence: 99%